Perbandingan Konsep Perkembangan Manusia dalam Filsafat Hegel dan Confucius - Kasanova, Ria; Rudiyanto, Mohammad (Universitas Insan Budi Utomo, 2025)
Human development is a theme that has long been a concern in various philosophical traditions. The philosophies of Hegel and Confucius offer two different yet complementary approaches to understanding the process of human development. Hegel, with his dialectical theory, views human development as a historical process that occurs through social conflict and changes in individual self-consciousness within the framework of history. According to Hegel, individuals can only achieve full self-awareness through interaction with society and larger social changes. Meanwhile, Confucius, in his morality and virtue-focused thought, viewed that human development lies in the formation of good moral character, which is reflected in harmonious social relationships and appreciation of virtuous values. This research aims to compare the two concepts of human development and explore the similarities and differences between the views of Hegel and Confucius. The results of the comparison show that both philosophers agree on the importance of social interaction in human development, although they differ in their focus Hegel emphasizes the role of history and social conflict, while Confucius emphasizes moral virtue and harmonious social relations. The findings show the relevance of both philosophies in the modern context, both in the fields of education, social ethics, and developmental psychology. The study also shows that the thoughts of Hegel and Confucius can be further applied to solve contemporary social problems such as social inequality and character building in a pluralistic society.